2013
DOI: 10.1038/ng.2855
|View full text |Cite
|
Sign up to set email alerts
|

Germline loss-of-function mutations in LZTR1 predispose to an inherited disorder of multiple schwannomas

Abstract: Constitutional SMARCB1 mutations at 22q11.23 have been found in ~50% of familial and <10% of sporadic schwannomatosis cases1. We sequenced highly conserved regions along 22q from eight individuals with schwannomatosis whose schwannomas involved somatic loss of one copy of 22q, encompassing SMARCB1 and NF2, with a different somatic mutation of the other NF2 allele in every schwannoma but no mutation of the remaining SMARCB1 allele in blood and tumor samples. LZTR1 germline mutations were identified in seven of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
225
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(236 citation statements)
references
References 57 publications
9
225
1
1
Order By: Relevance
“…The schwannomas in these individuals show a three-stage four-hit sequence with somatic loss of one copy of 22q together with inactivating somatic variants of NF2 on the remaining chromosome 22. 29,30 Agenesis or hypoplasia of the corpus callosum is associated with 22q12 deletions in two of the patients reported here, and in two previously described patients. 11,12 This region does not contain any known genes involved in corpus callosum development.…”
Section: Discussionmentioning
confidence: 54%
“…The schwannomas in these individuals show a three-stage four-hit sequence with somatic loss of one copy of 22q together with inactivating somatic variants of NF2 on the remaining chromosome 22. 29,30 Agenesis or hypoplasia of the corpus callosum is associated with 22q12 deletions in two of the patients reported here, and in two previously described patients. 11,12 This region does not contain any known genes involved in corpus callosum development.…”
Section: Discussionmentioning
confidence: 54%
“…To the Editor: First, we thank Trevisson et al 1 for their valuable contribution to this subject and their comments on our brief report. In our study, we reported a familiar schwannomatosis without mutations of SMARCB1/INI1/hSNF5 and LZTR, the two known causative genes for schwannomatosis.…”
Section: Coq6 and Schwannomatosis | Trevisson Et Almentioning
confidence: 99%
“…In fact, both genes act as oncosuppressors; accordingly, tumors from patients with schwannomatosis typically show biallelic loss of the NF2 gene and loss of heterozygosity of SMARCB1 or LZTR1 with retention of the germline mutation. 1 …”
mentioning
confidence: 99%
“…1,17 Mutations in this gene are also responsible for around 50% of familial schwannomatosis and 10% of sporadic schwannomatosis. 16 The exact mechanisms by which these mutations cause schwannomatosis are not well understood. Sestini et al described a 4-hit mechanism involving the genes SMARCB1 and NF2 in the development of schwannomatosis.…”
mentioning
confidence: 99%
“…15, 16 Hutter et al, after sequencing the schwannomatosis exome, suggested that even more gene mutations on chromosome 22 must exist to account for the cases of schwannomatosis when SMARCB1 and LZTR1 are excluded. 8 Zhang et al reported that perhaps mutations in COQ6 play a role in schwannomatosis development.…”
mentioning
confidence: 99%